Orthodontic Correction of a Mandibular Lateral Incisor and Canine Incomplete Transposition in the Permanent Dentition - Kadir Beycan; Nejat Erverdi (Galenos Yayinevi, 2015)
Transposition of teeth is a rare type of ectopic eruption and in incomplete transposition the crowns might be transposed, but the root apices still remain in their relatively normal positions. In this report, we describe the orthodontic treatment of a 17-year-old girl with mandibular left lateral incisor and canine incomplete transposition in which the involved teeth were repositioned to their normal anatomic position within the dental arch in an acceptable treatment time period. Treatment procedure, mechanics, and sequencing used and final results are described. The final outcome was stable after 18 months of retention.